Language learning strategies and motivation among religious secondary school students - Mat Teh, Kamarul Shukri; Embi, Mohamed Amin; Nik Yusoff, Nik Mohd Rahimi; Mahamod, Zamri (2009)
Studies have indicated that motivation is related to both a high frequency and an appropriate use of language learning strategies (Oxford & Nyikos 1989; Chamot et al. 1999; Macaro 2001). This study is designed to investigate the types and level of Arabic language learning motivation among Malaysian religious secondary school students. We also examine the relationship between the use of language learning strategies and language learning motivation. Data for the study were collected using selfreport questionnaires, including the adaptation Strategy Inventory for Language Learning (Oxford 1990) version 7.0 and the Language Learning Motivation section of the Affective Survey (Ehrman & Oxford 1991). The sample was comprised of 457 Form 4 students from thirteen religious secondary schools in Terengganu, Malaysia. Descriptive statistics, including Pearson and Kruskal Wallis tests, were used to examine the relationship between language learning strategy use and the level of language learning motivation. The results indicate that the students were moderately motivated and tended to have stronger integrative motivation than instrumental motivation. The students’ strategy use was strongly correlated with language learning motivation. Overall, language learners with higher levels of motivation possess a richer repertoire of strategies and employ these strategies more frequently than less motivated language learners.